Determinação sacarimétrica de caldos e melaços provenientes da cana-de-açúcar sem adição de clarificantes químicos - Zuza, Elder Polo (2015)
This work aims to evaluate the performance of an alternative procedure for the instrumental determination of sucrose in industrial sugar cane juices and molasses, using the polarization method as an alternative procedure that do not involves clarifying agents, taking data at 880 nm. Samples from extraction, treatment, evaporation and cooking were used to compare the results from the present proposed method and the conventional one. In the proposed procedure, the filtering auxiliary Celite® [SiO2] replaced the chemical clarifying agent, with advantages concerning costs and lower waste generation, resulting in diminished environmental impact. Sampling was limited to the availability of samples and of operators and the comparisons were performed using the average values as well as the standard deviations, based on paired t-Student test. Inter e intra-day assays were taken to evaluate the robustness of the proposed procedure. Different operators were involved in the measurements with both procedures in order to evaluate the reproducibility of the measurements and accuracy of the proposed method.